Body enhancement in teaching proposal to the subject with Autism Spectrum Syndrome - Montesano, Pietro; Peluso Cassese, Francesco; Tafuri, Domenico (Formazione & insegnamento, 2017)
The theoretical and diagnostic approaches to Autistic Syndrome have changed over the years following the results of clinical studies that have established the organic etiology as well as behavioral. It is still difficult to identify with certainty the cause of the disease but are more clear types of treatments to use. At scholastic level, the number of autistic children attending public schools has increased and intervention teaching techniques were perfected. Of particular importance is the enhancement of the body that silent body must become a living body capable of action and convey emotions limiting redundancies, stereos and establishing effective relationships.